2022
DOI: 10.1016/j.ajpc.2021.100303
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity and cardiovascular disease: Current trends and future directions

Abstract: Highlights Food insecurity and CVD share a circular association. Association may be stronger for racial/ethnic minorities and single mothers. Greater investment and organization are needed to address this association. Targeting food insecurity may reduce the nationwide burden of CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 83 publications
0
6
0
1
Order By: Relevance
“…These findings were somewhat surprising given the greater prevalence of food insecurity in Black and Hispanic adults than in White adults in the US. 3,14 It is widely accepted that food insecurity is associated with negative health outcomes largely through its effects on diet quality, 21,22 whereas this pathway may vary widely across racial and ethnic groups. Two previous studies from NHANES found that significant associations of food insecurity with poor-quality diet were observed in White individuals but not in Black and Hispanic individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were somewhat surprising given the greater prevalence of food insecurity in Black and Hispanic adults than in White adults in the US. 3,14 It is widely accepted that food insecurity is associated with negative health outcomes largely through its effects on diet quality, 21,22 whereas this pathway may vary widely across racial and ethnic groups. Two previous studies from NHANES found that significant associations of food insecurity with poor-quality diet were observed in White individuals but not in Black and Hispanic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The above information was self-reported and collected by standardized questionnaires. Previous studies have shown that food insecurity is associated with negative health outcomes through nutritional/anthropometric (body mass index [BMI] and diet quality), behavioral (smoking, heavy drinking, and physical inactivity), mental health (access to a mental health professional), access to care (routine place to go for health care), and chronic disease (diabetes, hypertension, CVD, and cancer) pathways 21,22 ; thus, it is not appropriate to adjust for the above factors in the analysis. However, as an exploratory analysis, we further adjusted the above potential mediators in multivariable analyses.…”
Section: Assessments Of Covariatesmentioning
confidence: 99%
“…La población de estudio presentó altas prevalencias de SP + OB, incluso por arriba de la media nacional (86.2% vs 72.4%) (Shamah et al, 2021). Con respecto a la malnutrición por exceso, evidenciado por indicadores antropométricos como el IMC, la circunferencia de cintura, cadera e índice de cintura talla, mostraron valores por arriba a los reportados en algunos otros estudios (Monroy 2021; Chang, 2022;Gómez, 2020;Liu, 2020;Raccanello, 2020). Aunque no se encontraron diferencias estadísticamente significativas entre niveles de IA y medidas antropométricas, se logró observar que la tendencia en la población fue que aquellas personas con inseguridad severa, tenían un IMC, circunferencia de cintura y un ICT mayores, lo cual es similar a lo observado en otros reportes de América Latina (Ruderman et al,2021) incrementando su RCV.…”
Section: Discussionunclassified
“…Social determinants of health (SDOH) include poverty level, food security level, home ownership, household education, access to a routine place for health care, health insurance status, and household head relationship status (Connolly et al, 2022). An inverse association has been found between CVD and adversity in each of these SDOHs (Singh et al, 2015), (Sims et al, 2020) (Chang et al, 2021), (Alcalá et al, 2015).…”
Section: Introductionmentioning
confidence: 99%